HydroMEA: A 3D Hydrogel‐Based Microfluidic Device to Study Electrophysiology for Myelinated Nerve‐on‐Chip - Blandine F. Clément; Cédric Pfister; Timothy Kurer; Nicole Baalbaki; Max Paxtian; Jeeho Sim; Céline Labouesse; Dhanajay V. Deshmukh; Julian Hengsteler; Julia Lehmann; Lorenza G. Paganella; Tobias Ruff; et al. (Advanced Healthcare Materials, 2026)
ABSTRACT Engineered in vitro platforms are powerful systems to study information flow in the nervous system. While existing polydimethylsiloxane (PDMS)‐based microfluidic platforms offer precise architectures, the cultured neurons grow on two‐dimensional (2D) planar multielectrode arrays (MEA). To mimic the native microenvironment, where neurons grow in three‐dimensional (3D) extracellular matrices (ECM), 3D hydrogels can be designed to encapsulate cells and enable physiologically mimicked behaviors. Here, we describe ‘hydroMEA,’ a 3D platform fabricated by placing PDMS microstructures on a high‐density MEA and filled with a desired hydrogel, to offer controlled topologies, physiologically relevant microenvironments, and real‐time electrophysiological measurements. First, we developed a gelatin methacryloyl (GelMA) hydrogel with incorporated ECM components and tuned the mechanical properties to match those of nerve tissue. The hydrogel was able to support: (1) the growth of iPSC‐derived sensory neurons (hSNs) for >100 days; (2) co‐cultures of hSN with human embryonic stem cell‐derived Schwann cells (hSCs), to enable reliable 3D myelination. Next, hydroMEA were prepared for topologically defined 3D growth and myelination in designated compartments. Finally, electrophysiological evaluation of hSN‐hSCs co‐cultures revealed increased conduction speeds indicating functional myelin. This platform is a promising tool to study cell‐cell interactions and to functionally evaluate the effect of pharmacological compounds in a more translational manner.